Mengembangkan Kecerdasan Kinestetik Melalui Senam Irama Apuse - Pratama, Leo; Hardianti Oktaviana; Aji Suryo Putro, Waskito (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Kinesthetic intelligence is the ability to use all parts of the body to convey ideas and feelings. Based on observations by researchers at TK Aisyiyah Bustanul Athfal 2 Aimas, children's kinesthetic intelligence has not developed. This study aims to develop the kinesthetic intelligence of early childhood at TK Aisyiyah Bustanul Athfal 2 Aimas through Apuse Rhythmic Gymnastics. This research method uses a descriptive qualitative approach, Data collection techniques using observation, interviews, and documentation. Based on the results of observations and interviews conducted by researchers, after conducting Apuse Rhythmic Gymnastics in early childhood at TK Aisyiyah Bustanul Athfal 2 Aimas, children's kinesthetic intelligence began to develop, this can be seen from before doing Apuse rhythmic gymnastics, children were still unable to stretch their arms properly and children were still confused when doing clapping movements to the right and left, but after 12 times doing Apuse rhythmic gymnastics, children were able to stretch their arms correctly, and when doing clapping movements to the right and left, children were able to follow the instructions correctly. The results of the study on developing kinesthetic intelligence through rhythmic gymnastics in early childhood at Aisyiyah Bustanul Athfal 2 Aimas Kindergarten can be concluded that rhythmic gymnastics activities can improve the development of kinesthetic intelligence in early childhood at Aisyiyah Bustanul Athfal 2 Aimas Kindergarten.